Hubungan Kualitas Pelayanan Dengan Kepuasan Pasien Poli Umum Puskesmas Mamburungan Kota Tarakan - Renna Youfristiya Sari; Sulidah Sulidah; Donny Tri Wahyudi; Maria Imaculata Ose; Fitriya Handayani; Gusni Fitri (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Satisfying excellent service will definitely have an impact on achieving a standard value of satisfaction for patients or service recipients. Patient satisfaction is the best assessment of the description of the diversity of service quality received by patients. This research was conducted with the aim of knowing the relationship between service quality and patient satisfaction at the general polyclinic at the Mamburungan Health Center, Tarakan City, by applying the RATER concept, namely responsiveness, assurance, tangible, empathy, and reliability. This research is descriptive quantitative using the Cross Sectional Study method conducted on 165 respondents, using a questionnaire, with the result that the quality of service is good, and patient satisfaction at the Mamburungan Health Center is satisfied. The results of the data analysis test Rho Spearman's P value (Sig. (2-tailed) 0.00 and α 0.05 which proves that there is a significant relationship between service quality and patient satisfaction in the general polyclinic at the Mamburungan Health Center, Tarakan City. It is hoped that the Mamburungan Public Health Center can further improve quality services by creating separate examination rooms so that patient privacy can be better maintained, not combining multiple services so that patient privacy and comfort can be increased, and building cleanliness, service rooms, tidiness, and the appearance of officers so that they can be further improved so that maximum patient satisfaction can be achieved.